Áreas de endemismo para espécies de mamíferos terrestres em um estado megadiverso na região central do Brasil - Ferreira, Ruth (2023)
Conserving biodiversity in the face of changes on natural landscapes that have caused irreparable disturbances to populations of many species, at local and regional geographic scales, has become a global concern. However, which elements of biodiversity should we conserve and in which areas, are frequently asked questions. Therefore, identifying geographic areas with high levels of diversity and endemism is critical to inform conservation decisions, in particular for groups of endangered organisms. In this study, we sought to identify areas of endemism using traditional metrics of taxonomic endemism, CWE and GIE; identify endemism areas using the phylogenetic endemism (PE) metric; identify and distinguish different types of endemism of mammalian communities using the CANAPE approach to distinguish between areas of neo- and paleo-endemism; and measure the number of endemism areas (neo- and paleoendemic) in conservation units (UC) and indigenous lands (TI) in the State. We identified several areas of endemism in the State using the different metrics. The CWE and GIE results were congruent in most endemism areas, except in the northeast region of the state. We also identified communities with high PE values concentrated on the State boundaries. Our results also showed that most communities depicted mixed endemism, a combination of elements that evolutionarily diverged recently and also older elements, distributed in portions of the three biomes present in the State. We identified that these areas with high endemism are poorly protected by the UCs and TIs currently present in the State. Our study highlights the importance of understanding the endemism patterns for terrestrial mammals in the State of Mato Grosso. The use of these metrics can provide solid information for conservation planning. Such information contributes to establishing priority conservation areas based on an estimate of unprotected high endemism areas in the State.